2021
DOI: 10.1002/er.6414
|View full text |Cite
|
Sign up to set email alerts
|

Organic sensitization of graphene oxide and reduced graphene oxide thin films for photovoltaic applications

Abstract: In this work, a new organic compound (K-Azo) was introduced to enhance the electrical and optical performance of graphene oxide (GO) and reduced GO (rGO) nanostructured films. The improved and modified chemical vapour method was employed for the synthesis of GO and rGO. The photophysical characterization of thin films was performed by applying analytical techniques including X-ray diffraction, Fourier-transform infrared spectroscopy, scanning electron microscopy, ultraviolet-visible, and Raman spectroscopy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Furthermore, hemoglobin takes oxygen from the lung and carries carbon dioxide to the lung, which may be utilized to diagnose thalassemia with a fractured index of 1.38. Consequently, plasma, or blood fluid, is applied for transporting different materials via the blood that may be employed to diagnose cardiovascular disease (CVD) [52]. Its RI value equals 1.35.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, hemoglobin takes oxygen from the lung and carries carbon dioxide to the lung, which may be utilized to diagnose thalassemia with a fractured index of 1.38. Consequently, plasma, or blood fluid, is applied for transporting different materials via the blood that may be employed to diagnose cardiovascular disease (CVD) [52]. Its RI value equals 1.35.…”
Section: Resultsmentioning
confidence: 99%
“…the blood that may be employed to diagnose cardiovascular disease (CVD) [52]. Its RI value equals 1.35.…”
Section: Resultsmentioning
confidence: 99%
“… 16 They also have high conductivity and a structure that can be made porous to build efficient supercapacitors 17 or enhance the performances of solar cells. 5 , 18 These graphene-like materials have also found applications in optics due to their nonlinear properties 19 , 20 and in medicine as a drug release matrix for targeting cancer cells. 21 However, the efficient use of GO and rGO in these applications can be limited by their arbitrary amount of lattice disorder, which is due to several key factors, including the fabrication technique.…”
Section: Introductionmentioning
confidence: 99%
“…Their challenge is to at least obtain a stable organic material that is also flexible and can be implemented [5][6][7] as an active layer in optoelectronic devices, especially organic solar cells. Actually, it has been reported that the architectures of the most efficient photovoltaic cells use alternating donor-acceptor groups [8][9][10][11][12][13], mainly for their good thermal stability. In this context, poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV) is a semiconducting polymer of interest [14][15][16], one that has been widely studied for the development of a P-N junction with [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) [17][18][19].…”
Section: Introductionmentioning
confidence: 99%